2012
DOI: 10.1080/09593330.2011.579183
|View full text |Cite
|
Sign up to set email alerts
|

CeO2mediated photocatalytic degradation studies of C.I. acid orange 7

Abstract: CeO2 nanoparticles were prepared by a simple precipitation method, followed by calcination treatment. By selecting photocatalytic degradation of acid orange 7 (AO7) as a probe reaction, the influences of calcination temperature of catalyst, the concentration of AO7, initial pH value of AO7 solution and catalyst dosage on the photocatalytic activity of CeO2 were studied. It was found that CeO2 calcined at 550 degrees C shows the highest photocatalytic activity under visible light irradiation. It was revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…The apparent rate constant of the CeO 2 micropillows estimated from the slope of a plot ln ( A 0 / A t ) versus t is 0.238 h –1 . The degradation rate of the CeO 2 micropillows is 87%, which is much higher than in reported literature 7, 10.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The apparent rate constant of the CeO 2 micropillows estimated from the slope of a plot ln ( A 0 / A t ) versus t is 0.238 h –1 . The degradation rate of the CeO 2 micropillows is 87%, which is much higher than in reported literature 7, 10.…”
Section: Resultscontrasting
confidence: 52%
“…Cerium oxide (CeO 2 ), a functional rare earth oxide with unique physical and chemical properties, has received greatest attention due to its extensive applications in environmental and energy related fields, gas sensors, ultraviolet (UV) blockers, oxygen storage capacitors, polishing materials, solid oxide fuel cells 3–6. Moreover, CeO 2 is an economical and relatively non‐toxic material similar to ZnO or TiO 2 and has been considered as an alternate material for the application in photocatalyst and photovoltaic cells 7–10. Recently, three‐dimensional (3D) micro or nanostructured materials derived from self‐assembly of nanoscale building blocks have significantly motivated the scientific attention due to their unique and novel functional properties 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes such as methylene blue (MB), methyl orange (MO), or acid orange 7 (AO7) are often used as general probes of photocatalytic decontamination activity. Various CeO 2 nanostructures, including nanowires 89 and nanoparticles 90,91 degrade these dyes under UV excitation. These studies generally implicate ROS photogenerated through CB electrons or VB holes in destruction of the dye molecules.…”
Section: Environmental Remediation/decontamination Reactionsmentioning
confidence: 99%
“…The difficulties associated with recyclability and removal of the catalyst holds back its commercial application for waste water treatment. As an ambient catalytic reaction, a heterogeneous Fenton -like oxidation on pure and modified ceria nanoparticles was attempted by researchers due to its merits over homogeneous catalysis [13,14]. In depth investigations of ceria/H 2 O 2 Fenton-like system revealed that the production of hydroxyl radicals mainly depends on the nature of the oxide surface.…”
Section: Introductionmentioning
confidence: 99%